Disaster policy and politics : emergency management and homeland security - Sylves, Richard Terry (SAGE ; CQ Press, 2020)
"In the Third Edition of Disaster Policy and Politics, author Richard Sylves provides much-needed contemporary coverage of the fields of disaster management and homeland security interspersed with mini-case studies of events such hurricanes Irma, Maria, and Harvey; Hawaii's nuclear attack false warning; and responses to U.S. wildfires. Paying special attention to the role of key actors--decision makers at the federal, state, and local levels; scientists; engineers; civil and military personnel; officials; and first responders--the author explores how physical and social science researchers contribute to and engage in disaster policy development and management. The book's comprehensive "all-hazards" approach introduces students to the important public policy, organizational management, and leadership issues they may need as future practitioners and leaders in the field. The text provides a concise history of the field, presents useful theories and concepts, poses thought-provoking questions, and is crafted to be both instructor- and student-friendly"- Resumé vydavatel
Terminologický slovník
Keywords: národní bezpečnost -- Spojené státy americké; vnitřní bezpečnost -- Spojené státy americké; krizový management -- Spojené státy americké; katastrofy -- Spojené státy americké; prevence katastrof -- Spojené státy americké; havarijní plánování -- Spojené státy americké; national security -- United States; internal security -- United States; crisis management -- United States; disasters -- United States; prevention of disasters -- United States; disaster planning -- United States; monografie; monographs